(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper delves into the intricate dynamics of the G20 Summit, examining its evolution, impact, and future directions within the realm of global governance. With a focus on addressing pressing global challenges, the G20 Summit serves as a pivotal forum where leaders from the world’s largest economies converge to foster dialogue, cooperation, and policy coordination. Originating as a response to the 2008 financial crisis, the G20 has expanded its agenda to encompass a diverse array of issues, including economic policy coordination, trade, sustainable development, and pandemic response. Through comprehensive evaluation and analysis, this paper aims to assess the effectiveness of G20 initiatives, identify key challenges facing the forum, and delineate potential pathways for enhancing its role in shaping the trajectory of international affairs. By shedding light on the complexities and opportunities inherent in the G20 Summit, this research contributes to a nuanced understanding of its significance within the broader landscape of global governance.